Process Implementation in Post-editing to Ensure Quality in Translation (Bridging Cultures, 2021)
The translation profession is constantly evolving and becoming more technological to meet the needs of the increasing demand for translation and localization services. The focus should not be on when human linguists will become obsolete, but rather on the competences needed to face this challenge. Thus, the improvement in the quality of Artificial Intelligence-enabled Translation and Machine Translation (MT) are taking over the forefront of technological advances and have compelled translators to adapt to new environments and to learn and adjust their own processes and requirements. To that purpose, it is imperative for Translation Service Providers (TSP) and linguists in general to learn and apply quality processes stipulated by ISO standards on Translation, Post-Editing, Terminography and Information Security Management System (ISMS).